1 July 1858: what Wallace knew; what Lyell thought he knew; what both he and Hooker took on trust; and what Charles Darwin never told them. (30th May 2013) - Davies, Roy
<x xml:space="preserve">Abstract</x> At the Linnean Society on 1 July 1858, Charles Lyell and Joseph Hooker, using only an extract from Charles Darwin's unpublished essay of 1844, and a copy of a recent letter to Asa Gray in Boston, argued successfully that Darwin understood how species originate long before a letter from Alfred Russel Wallace outlining his own version of the theory of evolution arrived at Darwin's home. That letter from Ternate in the Malay Archipelago, however, was not the first letter Darwin received from Wallace. This article will contend that two of the three letters Wallace sent Darwin between 10 October 1856 and 9 March 1858 arrived much earlier than Darwin recorded, thereby allowing him time to assess Wallace's ideas and claim an independent understanding of how the operation of divergence and extinction in the natural world leads strongly marked varieties to be identified as new species. By the time of the Linnean meeting Darwin's new ideas had filtered into his letters and 'big' species book, despite the absence of any independent evidence from the natural world to justify his constant insistence to have been guided only by inductive reasoning. © 2013 The Linnean Society of London, Biological Journal of the Linnean Society, 2013, 109, 725–736.